Expression Patterns and Correlations with Metabolic Markers of Zinc Transporters ZIP14 and ZNT1 in Obesity and Polycystic Ovary Syndrome - Maxel, Trine; Svendsen, Pernille Fog; Smidt, Kamille; Lauridsen, Jesper Krogh; Brock, Birgitte; Pedersen, Steen Bønlykke; Rungby, Jørgen; Larsen, Agnete (Frontiers in Endocrinology, 2017)
Polycystic ovary syndrome (PCOS) is associated with infertility, increased androgen levels and insulin resistance. In adipose tissue, zinc facilitates insulin signaling. Circulating zinc levels are altered in obesity, diabetes, and PCOS, and zinc supplementation can ameliorate metabolic disturbances in PCOS. In adipose tissue, expression of zinc influx transporter ZIP14 varies with body mass index (BMI), clinical markers of metabolic syndrome, and peroxisome proliferator-activated receptor gamma (PPARG). In this study, we investigated expression levels of ZIP14 and PPARG in subcutaneous adipose tissue of 36 PCOS women (17 lean and 19 obese women) compared with 23 healthy controls (7 lean and 16 obese women). Further, expression levels of zinc transporter ZIP9, a recently identified androgen receptor, and zinc efflux transporter ZNT1 were investigated, alongside lipid profile and markers of glucose metabolism (insulin degrading enzyme (IDE), retinol binding protein 4 (RBP4), and glucose transporter 4 (GLUT4)). We find that ZIP14 expression is reduced in obesity and positively correlates with PPARG expression, which is down-regulated with increasing BMI. ZNT1 is up-regulated in obesity, and both ZIP14 and ZNT1 expression significantly correlates with clinical markers of altered glucose metabolism. In addition, RBP4 and GLUT4 associate with obesity, but an association with PCOS as such was present only for PPARG and RBP4. ZIP14 and ZNT1 does not relate to clinical androgen status and ZIP9 is unaffected by all parameters investigated. In conclusion: our findings support the existence of a zinc dyshomeostasis in adipose tissue in metabolic disturbances- including PCOS-related obesity.